Should we burn or conserve? A case study of the Moxwera wa Babaso newspaper (1925-1938) - Loubser, Maggi (University of Pretoria, 2023)
Mini Dissertation (MSocSci (Tangible Heritage Conservation))--University of Pretoria, 2023.